2020
DOI: 10.1525/collabra.267
|View full text |Cite
|
Sign up to set email alerts
|

Is Healthy Neuroticism Associated with Chronic Conditions? A Coordinated Integrative Data Analysis

Abstract: Early investigations of the neuroticism by conscientiousness interaction with regards to health have been promising, but to date, there have been no systematic investigations of this interaction that account for the various personality measurement instruments, varying populations, or aspects of health. The current study-the second of three-uses a coordinated analysis approach to test the impact of the neuroticism by conscientiousness interaction on the prevalence and incidence of chronic conditions. Using 15 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 67 publications
2
17
1
1
Order By: Relevance
“…Personality traits have received increasing attention as a potential source of individual differences in health development (Weston et al, 2020). Personality is defined as relatively enduring patterns of thoughts, feelings, and behaviors that reflect the tendency to respond in certain ways under certain circumstances (Roberts, 2009).…”
Section: Theoretical Basis For the Longitudinal Association Between P...mentioning
confidence: 99%
“…Personality traits have received increasing attention as a potential source of individual differences in health development (Weston et al, 2020). Personality is defined as relatively enduring patterns of thoughts, feelings, and behaviors that reflect the tendency to respond in certain ways under certain circumstances (Roberts, 2009).…”
Section: Theoretical Basis For the Longitudinal Association Between P...mentioning
confidence: 99%
“…Other findings suggested that high neuroticism and low conscientiousness are associated with greater health‐risk behaviors (Vollrath & Torgersen, 2002). Such assertions regarding healthy neuroticism are still debatable, and previous studies have reported inconsistent mixed results (Weston, Graham, Turiano et al ., 2020). The present study was designed to explore this phenomenon among adolescents to see whether the nature of relationship between neuroticism and health‐risk behaviors differs for different levels of conscientiousness in them.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show no such interaction, e.g. for serious diseases that are likely to be genetic (Weston et al 2020;Turiano et al 2020), but also on precautionary behaviour in relation to COVID-19 (Aschwanden et al 2020).…”
Section: Personality and Educational Achievementmentioning
confidence: 93%